2021
DOI: 10.1186/s13072-021-00426-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethionine-mediated reduction of S-adenosylmethionine is responsible for the neural tube defects in the developing mouse embryo-mediated m6A modification and is involved in neural tube defects via modulating Wnt/β-catenin signaling pathway

Abstract: Neural tube defects (NTDs) remain one of the most life-threatening birth defects affecting infants. Most patients with NTDs eventually develop lifelong disability, which cause significant morbidity and mortality and seriously reduce the quality of life. Our previous study has found that ethionine inhibits cell viability by disrupting the balance between proliferation and apoptosis, and preventing neural stem cells from differentiating into neurons and astrocytes. However, how ethionine participates in the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Speci c differential expression of METTL13 and FTO and differential m 6 A methylation in different brain regions (medial prefrontal cortex and basolateral and central amygdala) were observed in mice during a stress response, which was consistent with the expression of glucocorticoids [29]. ALKBH5 overexpression inhibits cell proliferation via the Wnt/β-catenin signaling pathway, and METTL3 downregulation also reduces cell proliferation and increases apoptosis by inhibiting the Wnt/β-catenin signaling pathway [30]. METTL14 knockdown signi cantly reduced proliferation and promoted the differentiation of mouse embryonic neural stem cells, thereby inhibiting their self-renewal ability [31].…”
Section: Discussionsupporting
confidence: 61%
“…Speci c differential expression of METTL13 and FTO and differential m 6 A methylation in different brain regions (medial prefrontal cortex and basolateral and central amygdala) were observed in mice during a stress response, which was consistent with the expression of glucocorticoids [29]. ALKBH5 overexpression inhibits cell proliferation via the Wnt/β-catenin signaling pathway, and METTL3 downregulation also reduces cell proliferation and increases apoptosis by inhibiting the Wnt/β-catenin signaling pathway [30]. METTL14 knockdown signi cantly reduced proliferation and promoted the differentiation of mouse embryonic neural stem cells, thereby inhibiting their self-renewal ability [31].…”
Section: Discussionsupporting
confidence: 61%
“…The METTL3 -mediated m 6 A modification is essential for mammalian embryonic development ( Sui et al, 2020 ). A previous study has revealed that levels of m 6 A modification and METTL3 expression are lower in ethionine-induced NTD than in controls ( Zhang L. et al, 2021 ). Consistent with these findings, we found that the retinoic acid-induced NTD mouse model had dramatically decreased overall m 6 A levels and METTL3 expression levels than those in control mice.…”
Section: Discussionmentioning
confidence: 93%
“…It has been proposed that the intricate orchestration of neural stem cell processes including proliferation, migration, differentiation, and apoptosis is a key determinant in neural tube formation [50] . Studies have substantiated that neural tube disorders can arise from diminished proliferation and heightened apoptosis of neuroepithelial cells within the developing neural tube [ 51 , 52 ]. VPA exposure has been linked to fetal neural tube DNA damage and leads to downstream alterations, including cell cycle arrest and apoptosis [53] .…”
Section: Discussionmentioning
confidence: 99%